The Study Area - Donya Ahmadi; Tuna Tasan-Kok (A+BE: Architecture and the Built Environment, 2018)
Dominant narratives and discourses of diversity in Toronto have for long been predominantly based on ethnic origin and immigration due to the migration history and tradition in Canada which is increasingly reliant on immigration for population and labour market growth (Wayland, 2006). In Canada, national and city level diversity policies are often very different, although discourses at the federal level have an important impact upon city and even community-level efforts in addressing diversity in Toronto. A number of important shifts have taken place at the federal level with regards to diversity policy in the recent years when the Stephen Harper-led Conservative Party won the 2006 federal elections. These shifts include increased decentralization of administrative and financial responsibilities, cut-backs to federal funding of social programs, introduction of conservative values in public social services (especially concerning health issues, women and newcomers), changes in the Temporary Foreign Workers Program (TFWP), and immigration policy, all of which have impacted on policies at the local level (Russo, 2008; Caron and La Forest, 2009).